Established Education and Information in Cancer: The Future of Telemedicine - Gintoro, Harjanto Prabowo (Indonesian Journal of Cancer, 2008)
Established Education and Information in Cancer: The Future of TelemedicineÂ full text: http://www.scribd.com/doc/45151919/Established-Education-and-Information-in-Cancer-The-Future-of-Telemedicine